Three Sketches about the Decoration and Production of the Ananyino Ware (According to the Materials of 2017 Excavations on the Ust-Nechkinskoye I Settlement in the Middle Kama Region) - Mitryakov Aleksander E. (Археология евразийских степей, 2023)
The paper deals with some features of ware assemblage of the Ust-Nechkinskoye I hillfort in the Middle Kama region. A brief description of the complex is given, some characteristic features of the Ananyino ceramics are marked out, that are usually not taken into account in the formal statistical analysis of the assemblages. It is claimed that three features – the presence of pits, the "collar" on the part of the vessels and the slipshod decoration at a late stage of development may be considered as the elements that are more determined by the production technology and the life cycle of ware than as decorative patterns. In this regard, the question is raised about the method of features registration and giving them weighty reasoning in the formal and statistical analysis of complexes and comparing them with each other. It is assumed that as a result of reconstruction of the technological process and understanding of the economic and cultural context of the Ananyino pottery, researches should focus on those characteristics of ware that are due to cultural, but not to technological or economic differences between the ancient groups.